Literasi Sains dan Berpikir Kritis: Analisis Evaluasi Mahasiswa terhadap Sumber Daya Bioprospeksi Lokal - Linna Fitriani; Ria Dwi Jayati; Tomi Hidayat (Postgraduate, University of Mataram, 2025)
Scientific literacy and critical thinking skills are essential in higher education, especially in bioprospection courses, in understanding the potential of biological resources objectively and scientifically. This study aims to analyze the relationship between scientific literacy and students' critical thinking skills in evaluating the bioprospection potential of local biological resources. This study used a quantitative correlational method, with participants consisting of biology students taking the bioprospection course. Data were collected using a scientific literacy questionnaire and a critical thinking test. Data were analyzed using Pearson correlation tests and simple linear regression tests. The results showed a significant relationship between scientific literacy and critical thinking skills among biology students. Students with high levels of scientific literacy tended to evaluate the potential of local bioprospection resources better. Regression analysis showed that scientific literacy is an independent variable influencing students' critical thinking skills. Scientific literacy can improve the critical thinking abilities of biology students. These findings emphasize the importance of integrating scientific literacy into bioprospection courses in higher education.